2002
DOI: 10.4049/jimmunol.169.10.5761
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Classical and Novel Protein Kinase C Isoforms in the Response of Human Vγ9Vδ2 T Cells to Phosphate Antigens

Abstract: Human γδ T cells expressing the Vγ9Vδ2 gene segments are activated polyclonally by phosphoantigens found on a wide variety of pathogenic organisms. After ligand exposure, Vγ9Vδ2 T cells proliferate and rapidly secrete large amounts of cytokines and chemokines that contribute to the innate immune response to these pathogens. Neither APCs nor costimulatory molecules are required. In this study we examined whether these phosphoantigens activate protein kinase Cθ (PKCθ). This novel PKC isoform is essential for Ag … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 52 publications
2
18
0
Order By: Relevance
“…Analysis of the results for genes associated with the early activation of T cells, such as Fynbinding protein, immediate early response 3 gene, and CD25 expression, showed that either IPP or Abs to CD3 activated V␦2 T cells (Table I). As expected, we also noted potent up-regulation of a number of proinflammatory cytokines and chemokines, many of which have been extensively documented as targets of phosphate-Ag activation in these cells (22,34) (Table I and data not shown). However, the cDNA screen also showed up-regulation of mRNA for the VDR in cells that had been activated with either IPP or CD3 (Table I).…”
Section: Activation Of V␦2 ϩ T Cells With Phosphate-containing Ligandsupporting
confidence: 83%
See 1 more Smart Citation
“…Analysis of the results for genes associated with the early activation of T cells, such as Fynbinding protein, immediate early response 3 gene, and CD25 expression, showed that either IPP or Abs to CD3 activated V␦2 T cells (Table I). As expected, we also noted potent up-regulation of a number of proinflammatory cytokines and chemokines, many of which have been extensively documented as targets of phosphate-Ag activation in these cells (22,34) (Table I and data not shown). However, the cDNA screen also showed up-regulation of mRNA for the VDR in cells that had been activated with either IPP or CD3 (Table I).…”
Section: Activation Of V␦2 ϩ T Cells With Phosphate-containing Ligandsupporting
confidence: 83%
“…Use of human tissues was approved by the Committee on Clinical Investigation of the Albert Einstein College of Medicine. Long-term cultures of V␦2 ϩ cells were established by stimulating once with IPP (30 M; Sigma-Aldrich) and were maintained with 50 U/ml IL-2 (National Cancer Institute) as described (34). V␦2 expression was determined by FACS (clone B6; BD Pharmingen).…”
Section: Cell Preparation and Stimulationmentioning
confidence: 99%
“…To this end, PKCy is required for Notch3-dependent activation of the IKK complex. Therefore, we provide the first direct evidence, to our knowledge, that pre-TCR is able to regulate PKCy membrane translocation and activity, a property so far only described for a/b and g/d TCR Cipriani et al, 2002). Notably, such a pre-TCR activity is unveiled by Notch3 activation.…”
Section: Discussionmentioning
confidence: 85%
“…(Table I). The 8A(or 8B)-activation of p38 MAPK could be associated with a cAMP-independent pathway, several signal transduction events enumerated in various cell types and stimuli (42)(43)(44)(45)(46), being possible. Strikingly, the 8A/8B activation did not potentiate the p38 MAPK phosphorylation promoted by anti-CD3 or TNF-o.. A full activation of the p38 MAPK by anti-CD3 in y8 T cells (or TNF-o.…”
Section: Discussionmentioning
confidence: 99%